SCREENING OF HETEROCYCLIC COM POUNDS AS ANTIBACTERIAL AGENTS. J. SOME PYRAZOLE-4-CARBOXALDEHYDE DERIVATIVES: Short Communication (Biological Sciences - PJSIR, 2002)
Various derivatives  of heterocyclic  compounds  are usedin chemotherapy (Wilson et al 1972). Some of the derivatives of nitrofuran-2-carboxaldehyde such as Nitrofura ntoin and Ni trofurazone are excellent antibacterical agents